English reading strategies by students from Northern moutainous provinces at the Faculty of Information Technology, Thai Nguyen University - Phùng, Thị Thanh Tú (ĐHNN, 2017)
Classroom approaches to reading. Teaching reading strategies. Research on teaching and learning reading strategies in second language learning. FIT students' and teachers' opinions and reading strategies.